Relaxation techniques as an element supporting the functioning of the speech apparatus - a review of the literature - Bartecki, Nikodem; Strojek, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction The human speech apparatus is a complex system that relies on the cooperation of the respiratory, phonatory, articulatory and resonatory systems. Its proper functioning depends not only on physical condition patient, but also on mental state - particularly the level of tension and stress. In disorders such as tension dysphonia, stuttering, vocal overload or articulation difficulties, telaxation techniques have proven to be effective therapeutic interventions. Objective The aim of this article is to present knowledge about relaxation technigues that promote speech relaxation. These methods include progressive muscle relaxation, breathing exercises, laryngeal massage, biofeedback and mindfulness used in speech therapy and phoniatrics. A review of the literature indicates that the regular use of relaxation techniques improves phonatory quality, reduces muscular tension and may play an important role in the prevention of voice disorders. At te same time, the need for further research in this area is evident - particularly studies involving large sample sizes and the evaluation of long-term effects. Conclusions 1. Relaxation of the speech apparatus is an important element of both therapy and prevention of voice and speech disorders. 2. Research indicates that technigues such as progressive muscle relaxation, breathing exercises, laryngeal massage, biofeedback and mindfullness provide significant benefis for patients, including: reducing muscles tension, improving phonatory stability and achieving greater comfort in everyday communication. 3. Relaxation techniques can be beneficial in the treatment of seech therapy and phoniatric disorders: tension dysphonia, stutterin, articulation difficulties and vocal overload. 4. Relaxation of the seech apparatus plays a very important role in the prevention of voice disorders, especialyy among professional voice users.